1996 Manila film festival - del Mundo, Clodualdo A., Jr. (Animo Repository, 1996)
Communication Arts faculty Dr. Clodualdo del Mundo, Jr. won two awards in the 1996 Manila Film Festival. He copped the Best Story and Best Screenplay honors for the film Mulanay: Sa Pusod ng Paraiso which also won the Best Picture Award.